The Ideology of Christian Zionism As an Obstacle to Israeli-Palestinian Peace - Maryam Jamilah (As- Sakinah Law Firm & Society of Visual Informatics, 2026)
Christian Zionism has become one of the most influential religious-political ideologies shaping Western support for Israel, particularly in the United States. This article examines how Christian Zionist beliefs have contributed to the persistence of the Israeli–Palestinian conflict by providing theological and political legitimacy for unconditional support of Israel. Employing a qualitative literature review and historical analysis, the study traces the origins of Christian Zionism from the Protestant Reformation through nineteenth-century dispensationalism and explores its theological foundations, including Biblical Zionism and Dispensationalist Zionism. The findings demonstrate that Christian Zionist interpretations of biblical prophecy encourage political mobilization, financial assistance, and lobbying efforts in support of Israeli policies while reinforcing anti-Islamic narratives that deepen polarization and hinder prospects for peace. The study argues that the fusion of religious doctrine with foreign policy has transformed a territorial dispute into a broader religious and ideological confrontation, making conflict resolution increasingly difficult. It concludes that sustainable peace requires reframing the Israeli–Palestinian conflict as a political and territorial dispute rather than a theological struggle, while reducing external ideological intervention that perpetuates mutual hostility. This analysis highlights the significant role of transnational religious ideology in influencing international politics and the dynamics of protracted conflict.